PENGARUH WACC TERHADAP ROA DAN DER PADA PERUSAHAAN YANG TERDAFTAR DI BEI TAHUN 2015-2017 - Astrelia Crisentya Linardi; Alodya Agustina; Christofer Alimwiyono,; Eka Perdana; Guido Setiadi; Jurisa Jonathan; Leni Cynthia Dewi; Rony Joyo Negoro Octavianus (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2019)
The aim of this study is to determine the effect of Weighted Average Cost of Capital (WACC) on Return of Assets (ROA) and Debt to Equity Ratio (DER) in various company sectors. The population in this study are companies from various sectors listed on the Indonesia Stock Exchange (IDX) and the samples are 12 companies from various sectors. The results of this study indicate that between WACC(X) to ROA(Y1) and DER(Y2) does not have any significant relationship. It means that WACC(X) does not have a close relationship that affect ROA(Y1) and WACC(X) nor does it have a close relationship that affect DER(Y2). So it can be concluded thatWACC owned by the twelve companies did not significantly influence the ROA and DER of the 12 companies. The structure of cost capital does not affect thecompany's performance in terms of profitability and debt management.